The megalithic clusters of Deserto and Barrocal das Freiras (Montemor-o-Novo, Middle Alentejo) in the building of the sacred landscapes of ancient peasant societies of the 4th and 3rd millennia BCE - Gonçalves, Victor S. (2020)
The megalithic clusters of Deserto and Barrocal das Freiras are currently under study in the framework of the OMEGA research project. This group of monuments consists mostly of so-called “proto-megalithic” tombs, probably used around the mid-4th millennium BCE, possibly earlier. Other more evolved medium-to-large-sized monuments with differentiated Chamber and Corridor (passage graves), from the late 4th millennium and the first quarter of the 3rd millennium BCE, also exist in peripheral areas around the central clusters. This allows us to consider a centre-periphery development in building this space, with the earlier monuments located in the central area and the latest monuments located in its immediate surroundings. The study of the groups of Deserto and Barrocal das Freiras, taking in account both the architectural features of the monuments and the specificities of their votive sets, makes it possible to serialize the chronological and cultural levels of construction and use of these monuments, defining the building diagrams of the sacred places and the megalithic landscapes during the 4th and 3rd millennia BCE in Middle Alentejo.